2019
DOI: 10.3892/etm.2019.8161
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of plasmacytoid dendritic cells and Toll‑like receptor‑9 regarding the treatment efficacy of interferon‑α in HBeAg‑positive chronic hepatitis B patients

Abstract: Hepatitis B virus (HBV) infection represents a public health threat and a challenge for the medical community. Untimely treatment may lead to liver cirrhosis and even liver cancer. At present, the major treatment for hepatitis B e antigen (HBeAg)-positive chronic hepatitis B patients includes administration of interferon-α (IFN-α), which has anti-viral and immunomodulatory effects. Plasmacytoid dendritic cells (pDCs) and Toll-like receptor-9 (TLR-9) have important roles in anti-viral therapy. However, their pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…*P <.05, **P <.01 in CHB patients. 48,49 The dysfunction of DCs may reduce exogenous IFNα secretion and might also lead to non-responsiveness to IFNα treatment in CHB patients. 4 However, recent studies investigating the frequency and functionality status of DCs in CHB infection are still insufficient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…*P <.05, **P <.01 in CHB patients. 48,49 The dysfunction of DCs may reduce exogenous IFNα secretion and might also lead to non-responsiveness to IFNα treatment in CHB patients. 4 However, recent studies investigating the frequency and functionality status of DCs in CHB infection are still insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…However, the total levels of dendritic cells of responders and non‐responders were not significantly different prior to IFN‐α treatment ( P = .16), which is consistent with previous findings of peripheral blood DCs in CHB patients. 48 , 49 The dysfunction of DCs may reduce exogenous IFN‐α secretion and might also lead to non‐responsiveness to IFN‐α treatment in CHB patients. 4 However, recent studies investigating the frequency and functionality status of DCs in CHB infection are still insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Dendritic cells (DCs), serve as professional antigenpresenting cells (APC), play an important part in capturing and presenting antigens to T cells 19,20 . Previous studies showed that DCs could limit fibro-inflammatory injury in non-alcoholic steatohepatitis and DCs contributed to CCL4-induced liver fibrosis regression 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…China is a big country of liver disease (1-3). Statistics show that there are nearly 100 million people with chronic hepatitis B virus (HBV) infection in the country (4). Where, HBV infection rate is particularly high in Guangdong (5).…”
Section: Introductionmentioning
confidence: 99%
“…At present, treatment of hepatitis B mainly adopts antiviral drugs to improve inflammatory response and viral infection of liver tissues, thereby improving clinical symptoms(4)(5). However, there has been no perfect method for antiviral treatment of hepatitis B.…”
mentioning
confidence: 99%